Strategic public relations writing proven tactics and techniques - Eggensperger, Jim; Salvatore, Jeanne (New York, NY Routledge, 2022)
Putting strategy front and center, this public relations writing textbook coaches students to readiness for a career as an effective strategic communicator. The book focuses on the strategic aspect of public relations writing that distinguishes it from other writing, such as journalistic or academic. It highlights the essential types of writing necessary for effective public relations in multiple media channels, demonstrated by contemporary cases direct from practitioners working today. Overviews of the various tactical formats that must be mastered for powerful, strategic public relations-ranging from social media posts and website updates to podcasts, speeches and infographics-prepare students to be effective and up-to-date professionals. Full of examples and exercises, the book's strength is in its practical utility for career preparation and success. This text is suited to public relations writing courses at the undergraduate and postgraduate level, particularly those with a focus on strategy or that combine strategy and writing into one course. Online resources include a chapter outlines; a testbank; sample homework, paper and portfolio-building assignments and lecture slides. They can be accessed at www.routledge.com/ 9781032163871"--
Introduction -- Creating News -- Persuasive PR Writing -- Words Matter: Editing -- News Releases -- Media Kits: Media Advisories, Q&As. Bios, Fact Sheets and Corporate Profiles -- Pitching a Story -- Editorials and Op-eds -- Strategic Social Media -- Scripting Videos and Podcasts -- Speeches, Presentations & Media Interviews -- Blogs, Vlogs, and Newsletters -- Infographics and Data Displays -- Business Writing: Memos, Emails, Etcetera -- Key Elements of a PR Campaign.
Includes bibliographical references and index.
Keywords: Public relations; Public relations -- Authorship